1998
DOI: 10.1038/sj.onc.1201711
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability is correlated with telomere erosion and inactivation of G2 checkpoint function in human fibroblasts expressing human papillomavirus type 16 E6 oncoprotein

Abstract: Cell cycle checkpoints and tumor suppressor gene functions appear to be required for the maintenance of a stable genome in proliferating cells. In this study chromosomal destabilization was monitored in relation to telomere structure, lifespan control and G2 checkpoint function. Replicative senescence was inactivated in secondary cultures of human skin ®broblasts by expressing the human papillomavirus type 16 (HPV-16) E6 oncoprotein to inactivate p53. Chromosome aberrations were enumerated during in vitro agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…In those same mice, a strong correlation between telomere erosion and the number of anaphase bridges was found (Rudolph et al, 2001). Correlation between chromosomal instability and telomere erosion was demonstrated in human fibroblasts expressing HPV 16E6 (Filatov et al, 1998). In human keratinocyte clones expressing the HPV oncogenes 16E6 and 16E7, the frequency of anaphase bridges is dependent on the level of telomerase activity.…”
Section: Discussionmentioning
confidence: 75%
“…In those same mice, a strong correlation between telomere erosion and the number of anaphase bridges was found (Rudolph et al, 2001). Correlation between chromosomal instability and telomere erosion was demonstrated in human fibroblasts expressing HPV 16E6 (Filatov et al, 1998). In human keratinocyte clones expressing the HPV oncogenes 16E6 and 16E7, the frequency of anaphase bridges is dependent on the level of telomerase activity.…”
Section: Discussionmentioning
confidence: 75%
“…42 Although the E6-expressing cells are susceptible to endoreduplication when stressed with the spindle poisons colcemid and nocodazole 80,87 they spontaneously acquire polyploidy only after in vitro aging associated with attenuation and inactivation of DNA damage-responsive G2 checkpoint function. 42,80 This result suggested that reduced G2 checkpoint function in E6-expressing cells might produce stress on the mitotic spindle and thereby stimulate endoreduplication. The results described above suggested a model that explains how G2 checkpoint function limits stress on the mitotic spindle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…84 The inactivation of G2 checkpoint function that accompanies cellular aging in the HPV16E6-expressing fibroblasts appears to be a response to chromatid damage associated with telomere erosion and formation of unstable dicentric chromosomes. 80,85 Cells lacking G2 checkpoint function gain a growth advantage by being able to progress into mitosis with damaged chromatids. Induction of telomerase before E6-expressing cells acquired chromosomal instability preserved G2 checkpoint function and stabilized chromosomes ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of IMR-90 normal lung ®broblasts entering mitosis after exposure to ionizing radiation was much higher after expression of HPV-E6, suggesting that p53 is required for G2 arrest . In contrast the expression of HPV-E6 in human foreskin ®broblasts did not a ect G2 arrest in response to ionizing radiation initially (Filatov et al, 1998;Kaufmann et al, 1997;Passalaris et al, 1999;Paules et al, 1995). However, as early as 12 population doublings after the expression of HPV-E6 many cells entered mitosis after exposure to ionizing radiation (Kaufmann et al, 1997), and the G2 arrest in response to DNA damage was completely lost upon more extensive in vitro propagation (Filatov et al, 1998;Kaufmann et al, 1997).…”
mentioning
confidence: 99%